(3GdLGeY GdUZjQ aj aQhY GdMfGHdIs - (3eMeO Hf GdMSjf Hf eMeO Hf Nda GHf GdaQGA, CHh jYdj,J (B458 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe QMeg Gddg CeG HYO aEf eTjNfG QMege Gddg cGfhG jYXehf gPG GdcJGH JYXjekG hjbOehf Ydi SGFQ GdcJH JbOjekG s
(3BNQgG (B:s
(3aMjfFmP jdReg Gdcd dhbhY GdMGLI bGd Gddg YR hLd EfaQO hENaGbkG hKfGA dG GdBjI aCeG eG jYe GdabjQ aEfg jSY JQcg hGddg GYde s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B254s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B564s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs